„Dane z ulicy” – propozycje i sugestie na temat wykorzystania materiałów z procesów partycypacyjnych - Brzeziński, Kamil (Człowiek i Społeczeństwo, 2019)
Participation has gained enormous popularity in Poland in recent years. More and more local authorities – mostly due to the influence of city activists – are decided to: conduct public consultation, implement participatory budgeting and other forms and tools involving residents in co-decision processes on city issues. A huge number of data sets and reports are the results of these activities. It is assumed that loads of these documents might be an easily accessible data source for urban researchers. This paper presents own way and experience of using data from participatory budgeting conducted in Łódź, as well as some suggestions and possibilities of using data obtained by participatory techniques. Kamil Brzeziński, „Dane z ulicy” – propozycje i sugestie na temat wykorzystania materiałów z procesów partycypacyjnych [„Street data” – some suggestions on the use of data from participatory processes] edited by M. Nowak, „Człowiek i Społeczeństwo” vol. XLVIII: Kuchnia badań miejskich. Studia na temat praktyki empirycznej badaczy miasta [A backstage of urban research. Studies on the empirical practices of city research scientists], Poznań 2019, pp. 35–54, Adam Mickiewicz University. ISSN 0239-3271. Kamil Brzeziński, Uniwersytet Łódzki, Katedra Socjologii Wsi i Miasta, ul. Rewolucji 1905 r. nr 41, 90-214 Łódź, kamil.brzezinski@uni.lodz.pl